Driving Engagement: How Information Quality and Event Marketing Shape Toll Road Companies' Image on Instagram - Poetry, Salfhaoctha Friemay Aliefia; Ganiem, Leila Mona; Tomohardjo, Irmulansati (Journal of Dialogos, 2025)
PT Jasa Marga, as a company in the field of transportation services and toll road management infrastructure in Indonesia, faces the challenge of understanding and utilizing the potential of social media to build a positive corporate image. Pre-surveys to followers indicate a fairly good understanding of the company's basic information, but need improvement in certain information such as rest areas, toll rate discounts, and "Jumat Kuis" programs. This research aims to provide new insights and strategic guidance for PT Jasa Marga in building and maintaining its corporate image through Instagram considering that a positive corporate image can increase public trust in the company, from this trust which will ensure that toll road users will feel safe and comfortable using the services provided, especially toll road services. This study used Stimulus-Response theory. This study uses quantitative methodology, positivism paradigm, with explanatory research type, using survey methods and simple linear regression analysis tests. Data from this study was taken through a google form survey with respondents as many as 100 Instagram followers @official.jasamarga. The results of this study show that the Sig (2-tailed) value between the variables of information quality and event marketing with the image of each company is 0.000 where this value is smaller than 0.005 and it can be concluded that there is a significant relationship between the variables of information quality and event marketing on the company's image. Informative content is recognized as important in shaping positive perceptions, while event marketing strategies such as "Jumat Kuis" are effective in building positive interactions. Nevertheless, the study highlights areas that need further attention, such as increasing information related to rest areas and toll tariff discounts in the content presented.